Analisis Kebijakan Perumahan Subsidi di Indonesia Policy Analysis 0f Subsidized Housing In Indonesia - Adawiyah , Nur; Sihombing, Josua Adrio; Mar'ah, Sakinatul; Kemala , Putri (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The purpose of this research is to know the development of subsidy policy in the field of housing in Indonesia, and to know the obstacles that hinder the development of subsidized housing in Indonesia. This research is normative legal research, namely research conducted by examining secondary data (literature) consisting of: primary legal materials; secondary legal materials. In normative legal research, the data that has been collected, both through the inventory of primary legal materials and the search for secondary materials, content analysis is carried out which is then processed into general premises about general norms in the regulation of subsidies in the housing sector. Furthermore, it is analyzed deductively by using a syllogism thinking pattern composed of two statements (major premise and minor premise) and a conclusion. Conclusion: 1) the provision of subsidies to low-income people is expected to realize the community, especially low-income people to own a house; 2) the low absorption rate of subsidized housing